Macroeconomic Variables and Foreign Direct Investment Inflows in Turkey - Saliha Meftah; Abdelkader Nassour (Signifikan: Jurnal Ilmu Ekonomi, 2019)
Foreign direct investment (FDI) is an essential factor in the development of a country. This study aims to examine what factors influence foreign direct investment. By using the vector error correction model, the research shows that there is a long-term causality relationship between exchange rates and inflation with FDI. However, in the short term, there are no variables that affect FDI. Besides, the Granger causality test shows causality in the direction of GDP and FDI, while other variables do not have causality. This research has implications for policymakers to pay attention to macroeconomic variables in increasing the flow of foreign direct investment.